The Role of Rapid TEVAR in a Complex Ruptured Ascending Aortic Aneurysm - Sukanto, Daud Yudhistira; Limanto, Danang Himawan (Journal of Neonatal Surgery, 2025)
Background: Thoracic Endovascular Aortic Repair (TEVAR) is a minimally invasive procedure used to manage acute aortic dissection. The timing of intervention is critical, especially in cases requiring rapid response due to life-threatening complications. Methods: In this case report we collect the patient’s data through the mean of interviews, observations, and analysis of patient’s medical record. Results: A female patient in her 60s came to our ER with chief complaint of shortness of breath. Several examinations revealed a ruptured aneurysm in the ascending aorta, accompanied by compression atelectasis in the right middle and lower lobes. Unstable hemodynamics were found throughout the hospitalization period, thus a decision was made to proceed with rapid ventricular pacing TEVAR. The successful deployment of a thoracic stent graft temporarily stabilized the aortic dissection, but the patient's overall condition continued to decline postoperatively. The presence of other significant comorbidities, including possible mycotic aneurysm and metastatic disease, further complicated the management. The patient ultimately passed away on the fourth day of treatment. Conclusion: This case underscores the critical importance of timely intervention in acute aortic emergencies and highlights the challenges in managing patients with complex and advanced pathologies, even with the use of advanced minimally invasive techniques like TEVAR. The outcome also reflects the limitations of medical intervention in the context of multiple severe comorbidities, emphasizing the need for comprehensive and multidisciplinary approaches in similar cases.